PEMANFAATAN SURAT KETERANGAN ASAL INDONESIA DALAM PENINGKATAN INVESTASI BERORIENTASI EKSPOR AUSTRALIA KE INDONESIA - Sidabutar, Victor Tulus Pangapoi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2020)
Indonesia has signed a trade agreement with Australia and hoped that this agreement can benefit both parties in facing global free trade. Indonesia is not Australia's main trading partner currently and Indonesia's exports to Australia tend to decline in recent years. Indonesia can take advantage of Australia's export market which is experiencing an increase in the value of exports which has risen faster than import prices which has affected the growth of the Australian economy. Indonesia can utilize the export market, especially markets that have trade agreements with Indonesia in order to indirectly increase Indonesian exports by utilizing the issuance of Certificates of Origin from Indonesia as partners of producers of Australian export products. The abundance of natural resources and labor in Indonesia is expected to attract the interest of Australia to invest in Indonesia to build an industry that aims to produce goods for the needs of the country's export market demand and for Indonesia to increase the entry of foreign direct investment to Indonesia.